Role of Responsible Leadership for Organizational Citizenship Behavior for the Environment in Light of Psychological Ownership and Employee Environmental Commitment: A Moderated Mediation Model - Abbas, Ali; Chengang, Ye; Zhuo, Sufan; Bilal,; Manzoor, Shahid; Ullah, Irfan; Mughal, Yasir Hayat (Frontiers in Psychology, 2022)
The world is looking towards organizations for social responsibility to contribute to a sustainable environment. Employees’ organizational citizenship behavior for the environment (OCBE) is a voluntary environmental-oriented behavior that is important for organizations’ environmental performance. Based on social learning theory, the study examined the effects of responsible leadership in connection with OCBE by using a sample of 520 employees of manufacturing and service sector including engine manufacturing, petroleum plants banking and insurance sector organizations of China. Further, the role of psychological ownership and employee environmental commitment were used as mediators and moderators simultaneously. The direct, mediation, and moderation model results exposed a positive relationship between responsible leadership and OCBE via employee psychological ownership and employee environmental commitment. The study also revealed that the indirect effect is stronger when employees hold higher employee environmental commitment. The theoretical and practical implications for environmental sustainability in respect of organizations as well as future research directions are discussed.